Inflammation as a determinant of healing response after coronary stent implantation - Ochijewicz, Dorota (Int J Cardiovasc Imaging, 2021)
Cardiovascular disease remains the leading cause of death and morbidity worldwide. Inflammation plays an important role in the development of atherosclerosis and is associated with adverse clinical outcomes in patients after percutaneous coronary interventions. Data on stent elements that lead to excessive inflammatory response, proper identification of high–risk patients, prevention and treatment targeting residual inflammatory risk are limited. This review aims to present the role of inflammation in the context of evolving stent technologies and appraise the potential imaging modalities in detection of inflammatory response and anti-inflammatory therapies.